Specific Processes of Intelligence and Relationships in Academic Learning (SPIRAL) - Blankson, A. Nayena (Frontiers in Education, 2022)
We live in an age of cancel culture. Things are cancelled sometimes for important reasons and sometimes for superficial reasons. Over 100 years since its inception, the concept of IQ still lingers. Here, I make the argument that IQ should be cancelled. I conclude with the proposition of a new theory, Specific Processes of Intelligence and Relationships in Academic Learning (SPIRAL), which can be used to guide future research on cognition and achievement.